ChemInform Abstract: Mesoporous Cross‐Linked Polymer Copolymerized with Chiral BINAP Ligand Coordinated to a Ruthenium Species as an Efficient Heterogeneous Catalyst for Asymmetric Hydrogenation. Issue 9 (5th March 2013) - Sun, Qi; Meng, Xiangju; Liu, Xiao; Zhang, Xiaoming; Yang, Yan; Yang, Qihua; Xiao, Feng‐Shou
Abstract A heterogeneous chiral catalyst, obtained by copolymerization of divinylbenzene with a chiral BINAP ligand followed by coordination of the BINAP ligand with a ruthenium species, exhibits high activity, excellent enantioselectivity and extraordinary recyclability in asymmetric hydrogenation of β‐keto esters.